Intrathoracic rupture of hydatid cyst of the liver in children: a report of two cases - Rachida Laamiri; Sahla Sellami; Nahla Kechiche; Mabrouk Abdelaali; Mongi Mekki; Mohsen Belghith (Egyptian Liver Journal, 2021)
Abstract Background Intrathoracic rupture of hepatic hydatid cyst is a rare but dangerous complication. Its occurrence in children is exceptional as diagnosis and management constitute real challenges. We report two cases of intrathoracic rupture of hepatic hydatid cyst in children. Case presentation Our patients were respectively 12-year-old boy and 9-year-old girl, known cases of respiratory symptoms, diagnosed initially for pleuropneumonia. The CT scan established the diagnosis of intrathoracic rupture of hepatic hydatid cyst in the pleural cavity for the first patient and in the bronchial tree for the second. An emergency surgery was performed for both. The second patient developed broncho-biliary fistulas during the post-operative course which necessitated a re-intervention. A recurrence was noted at follow-up for the second patient. Conclusion Intrathoracic rupture of hepatic hydatid cyst is a serious complication which can occur even in children. Its diagnosis needs a high index of suspicion. The surgical approach remains controversial and there is a lack of consensus about the best way of management. Recurrence may occur despite appropriate treatment.